Independência do Banco Central: teoria e prática - Borges, Yasmin Fuentes de Freitas (2016)
The central bank independence theory emerged in the 1990s as an alternative to conducting monetary policy in a way that would reduce the government participation in the economy. Initial empirical studies have shown an inverse relation between the degree of central bank independence and the price level, which corroborated with the theoretical arguments by representatives who supported the theory. However, subsequent surveys have generated doubts and questions regarding central bank independence theory, including several reinterpretations of the theory. Along the four sections presented here, this research seeks consolidate the main arguments which the theory is grounded and score any criticism of the models. More specifically will analyze how it operates the independence of the central bank in Brazil, with the Central Bank of Brazil. The results presented by the survey highlight the ideological content that engages the debate around the independence of the central bank and points out that although the models are developed as close to reality as possible, there is no recipe for the conduct of monetary policy